Z Score Comparative Analysis of Tourism, Restaurant and Hotel Sub-Sector Companies Listed on The Indonesia Stock Exchange Before and After The Implementation of The Covid-19 Vaccine Policytittle - Chairun Amallia; Widya Rahmawati; Trio Candra Yoga; Likanopa Syentia (Lembaga Riset dan Inovasi Al-Matani, 2023)
The purpose of this study was to determine the impact of vaccine policy implementation on financial performance in terms of the Z-Score value of Tourism, Restaurant and Hotel sub-sector companies listed on the Indonesia Stock Exchange. This type of research is descriptive (descriptive research). The sampling technique in this study was a purposive sampling technique. The sample in this study are Tourism, Restaurant and Hotel Sub-Sector Companies listed on the Indonesia Stock Exchange which issue financial reports for 2020-2021. This study uses secondary data, namely annual financial reports. The analysis technique used is an event study which aims to analyze the differences in the company's Z-Score before and after the Covid-19 Vaccine Policy. The results of this study showed that there was no significant difference in the z score of the tourism, restaurant and hotel sub-sector companies before and after the Covid-19 vaccine policy.